SEISMIC BEHAVIOUR OF R.C.C BUILDING WITH AND WITHOUT FLOATING COLUMNS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main purpose of the project is to study the seismic behaviour of R.C.C building with and without floating column,G+5 structures has been selected for carrying out the project work. The building models are generated using software STAAD. Pro 8V. Seismic behaviour of structures or buildings subjected to earthquake induced motions and vibrations. They are transferred to the structures from the soil. A column is supposed to be a vertical member starting from foundation level and transferring the load to the ground. The term floating column is also a vertical element which at its lower level rests on a beam which is a horizontal member. Buildings with columns that hang or float on beams at an intermediate story and do not go all the way to the foundation, have discontinuities in the load transfer path.